Peningkatan Kompetensi Menulis Teks Recount Bahasa Inggris melalui Metode 'Cool Wae' pada Siswa Sekolah Menengah Pertama - Wijokongko, Wijokongko (Jurnal Didaktika Pendidikan Dasar, 2018)
The objective of this research is to improve the Junior Secondary School students in writing the English recount texts through “CooLWAE“ (Cooperative Learning WhatsApp Electronic). This classroom action research with three cycles was conducted to the first semester students at VIII C academic year 2016/2017 at the State Junior Secondary School in Pakem Sleman. The research subjects included 32 students altogether. Data were collected using observation checklist, test, questionnaire, document, and anecdotal record. The obtained data were analyzed descriptively, based on the performance indicator as ≥ 75% achievement in writing recount texts in English. Results show that “Cool WAE Method could improve the students’ recount text writing competency. The performance indicators in writing recount texts consisted of: choosing clear idea, developing coherent paragraph, structuring sentence, constructing grammatical sentence,   and using appropriate diction.   The students’ mean score in writing recount text improved from 54.23 in pre-cycle to 62.51 in cycle 1; 62.51 improved to 74.96 in cycle 2 ; and 74.96 improved to 76.37 in cycle 3.